Reversible Loading of Nanoscale Elements on a Multicomponent Supramolecular Polymer System by Using DNA Strand Displacement - Noteborn, Willem E. M. (Chembiochem, 2017)
Nucleic acids are excellent building blocks to enable switchable character in supramolecular polymer materials because of their inherent dynamic character and potential for orthogonal self‐assembly. Herein, DNA‐grafted squaramide bola‐amphiphiles are used in a multicomponent supramolecular polymer system and it is shown that they can be addressed by DNAlabeled gold nanoparticles (5 and 15 nm) through sequence complementarity. These nanoparticles can be selectively erased or rewritten on‐demand by means of DNA‐strand displacement.